Determination of nitrification and denitrification performance in antibiotic (tetracycline/chlortetracycline) and pain relief (paracetamol) effect in the SBR system - Çelik, Aytekin (Nigde Omer Halisdemir University, 2021)
Antibiotics and painkillers, like other pharmaceutics, negatively affect biological life in the aquatic environment. For this purpose, it is important to remove such pollutants from their aquatic or environment. In this study, the effects of tetracycline/paracetamol and chlortet racycline / paracetamol on nitrification and denitrification were investigated by simultaneously giving to the SBR process. Two separate reactors were used in the study and a total of 9 periods were applied. In the presence of tetracycline/paracetamol and chlortetracycline/ para cetamol, nitrification was most affected under the 6th condition and nitrification efficiency was determined around 33%. Likewise, the NO_2-N accumulation in the 6th condition is very high compared to other conditions and has been observed around 8.5mg/L. Denitrification in the presence of tetracycline/paracetamol and chlortetracycline/ paracetamol was most affected in the 9th condition and denitrification efficiency of around 1% was achieved in this condition. As a result, nitrification and denitrification efficiency under tetracycline/paracetamol and chlortet racycline/paracetamol were found to adversely affect nitrifiye and denitrifiye bacteria during low hydraulic detention times and concentrations of TC/PCT and CTC/PCT above 100 mg/L

Antibiyotikler ve ağrı kesiciler diğer farmasotikler gibi sucul ortamda biyolojik yaşama olumsuz yönde etki etmektedir. Bu amaçla bu tür kirleticilerin sucul veya bulundukları ortamdan giderilmesi önem arz etmektedir. Bu çalışmada, tetrasiklin/parasetamol ve klortetrasiklin /parasetamol ikilisinin SBR prosesine eş zamanlı verilmesi ile nitrifikasyon ve denitrifikasyon üzerine ne gibi etkileri olduğu araştırılmıştır. Çalışmada iki ayrı reaktör kullanılmıştır, ve toplam da 9 periyot uygulanarak yürütülmüştür. Tetrasiklin/parasetamol ve klortetrasiklin /parasetamol varlığında nitrifikasyon en çok 6. şartta etkilenmiş olup, nitrifikasyon verimi %33 civarında tespit edilmiştir. Aynı şekilde 6. şarttaki NO_2-N birikimi de diğer şartlara göre çok yüksek olup, 8.5 mg/L civarında gözlenmiştir. Tetrasiklin/parasetamol ve klortetrasiklin/ parasetamol varlığında denitrifikasyon ise en çok 9. şartta etkilenmiş olup, bu şartta %1 civarında denitrifikasyon verimi elde edilmiştir. Sonuç olarak, Tetrasiklin/ parasetamol ve klortetrasiklin/parasetamol ikilisi altındaki nitrifikasyon ve denitrifikasyon verimi, düşük hidrolik alıkonma sürelerinde ve 100 mg/L üzeri TC/PCT ve CTC/PCT konsantrasyonlarında nitrifiye ve denitrifiye bakterilerine olumsuz yönde etki ettiği belirlenmiştir.
SBR sisteminin antibiyotik (tetrasiklin/klortetrasiklin) ve ağrı kesici (parasetamol) etkisinde nitrifikasyon ve denitrifikasyon performansının belirlenmesi
Keywords: Environmental Engineering; Çevre Mühendisliği